A Sensitive UPLC-MS/MS Method for the Determination of Flurbiprofen in Rat Plasma: Application to Real Sample. (22nd April 2021) - Yaman, Mehmet Emrah; Atila, Alptug; Akman, Tugrul Cagri; Albayrak, Mevlut; Kadioglu, Yucel; Halici, Zekai
Abstract: For the quantification of flurbiprofen in rat plasma, a simple UPLC-MS/MS method with high sensitivity and short retention time for flurbiprofen was developed and validated using specific parameters. Etodolac was used as internal standard. The transitions (precursor to the product) of flurbiprofen and internal standard were obtained using the electrospray ionization in the negative ion multiple reaction monitoring mode, 243.2 → 199.2, 286.2 → 212.1, respectively. For chromatographic separation, C18 column was used for the stationary phase and gradient elution was used for the mobile phase. This mobile phase consisted of a methanol (A) and a 5 mM ammonium formate solution (B), which varied at a flow rate of 0.4 mL/min. For flurbiprofen, LLOQ was determined as 5 ng/mL. Quantification of flurbiprofen in the rat plasma with a linear calibration curve of 5–5000 ng/mL (r > 0.9991 for plasma) is possible with a retention time of 1.89 min. The total analysis time of the method was 3 min. The proposed method was validated. The intraday and inter-day precision (RSD%) and accuracy (RE%) were within 10% in all cases for flurbiprofen. The stability of flurbiprofen was evaluated under conditions such as short-term, long-term, autosampler and freeze/thaw. After method validation, flurbiprofen was succesfully quantified in real rat plasma samples.